2014
DOI: 10.1177/0961203314528556
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels in Jamaican patients with systemic lupus erythematosus

Abstract: Vitamin D has important effects on the immune system as it has been shown to exert antiproliferative and relative immunosuppressant effects. Low levels of this hormone may contribute to the immune activation in systemic lupus erythematosus (SLE) and other autoimmune diseases. Serum levels of 25-OH vitamin D were measured in 75 patients with SLE in Jamaica, using an enzyme-linked immunoassay. Correlations with clinical data and disease activity as determined by the BILAG index were determined. Of a total of 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…The distribution of 25-OH VD levels in the Hopkins and Jamaican cohorts were strikingly similar, mean levels in each cohort falling below what is considered the normal reference value of 30ng/ml (18). The observed high prevalence of vitamin D deficiency and insufficiency in these cohorts has been shown in previous studies of both cohorts (12, 19) as well as in other independent studies. It is a common finding that transcends differences in ethnicity (20) and has largely been thought to occur as a result of disease activity limiting nutritional intake and sunlight exposure.…”
Section: Discussionsupporting
confidence: 84%
“…The distribution of 25-OH VD levels in the Hopkins and Jamaican cohorts were strikingly similar, mean levels in each cohort falling below what is considered the normal reference value of 30ng/ml (18). The observed high prevalence of vitamin D deficiency and insufficiency in these cohorts has been shown in previous studies of both cohorts (12, 19) as well as in other independent studies. It is a common finding that transcends differences in ethnicity (20) and has largely been thought to occur as a result of disease activity limiting nutritional intake and sunlight exposure.…”
Section: Discussionsupporting
confidence: 84%
“…Our findings are consistent with several other observational studies that have shown that vitamin D level inversely correlates with disease activity. 7–9 16 21 22 27–29 In the longitudinal follow-up, univariable analysis showed significant associations of vitamin D with subsequent increases in SLEDAI-2K or high disease activity (SLEDAI-2K >10), each with ORs greater than 3. The predictive effect of low vitamin D on subsequent disease activity did not remain significant after adjustment for vitamin D supplementation, glucocorticoid use and immunosuppressive use, suggesting that in future studies of vitamin D effects in SLE, these variables should be controlled for.…”
Section: Discussionmentioning
confidence: 99%
“… 19 20 The frequency of vitamin D deficiency varies greatly between communities in different latitudes. 7 9 16 21 22 Currently, it is not yet known whether observations made in a certain location are applicable globally. Moreover, knowledge about the impact on SLE of vitamin D supplementation, often given to SLE patients as part of a preventive approach to osteoporosis or in an attempt to treat vitamin D deficiency, is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A significantly high prevalence of vitamin D deficiency has been observed in patients with SLE in Saudi Arabia ( 114 ), Bahrain ( 115 ), the USA ( 116 , 117 ), Canada ( 118 ), Jamaica ( 119 ), Brazil ( 120 ), France ( 121 ), Hungary ( 122 ), Denmark ( 123 ), and Spain ( 124 , 125 ). In clinical studies on patients with SLE, significant inverse correlations were observed between serum levels of vitamin D and SLE disease activity index (SLEDAI) score in Malaysian ( 126 ), Taiwanese ( 127 ), Thai ( 128 ), Indian ( 129 ), Egyptian ( 130 , 131 ), Saudi Arabian ( 132 ), Brazilian ( 133 , 134 ), Australian ( 135 ), American ( 136 ), Hungarian ( 122 ), and Chinese ( 137 ) populations with an exception of Serbian SLE subjects ( n = 46) ( 138 ).…”
Section: Micronutrientsmentioning
confidence: 99%